Experimental study of the dynamic behavior of a log boom employed at hydropower plants. - Castro, Felipe Santos de (2021)
The incidence of wooden debris in Santo Antônio hydropower plant (HPP) is a major issue to be addressed in order to avoid its own reduction efficiency. Log booms are floating structures assembled to form barriers upstream of the plant to protect its machinery, mainly against wood logs. Given their huge proportions and the turbulent environment where they operate, to understand its dynamics and movements is very important to achieve better performances in terms of design and operation. The use of experimental techniques to simulate the hydrodynamics response of log booms, with and without debris,can provide significant results to estimate their dynamic behavior. This study proposes to design and conduct hydrodynamic tests using scale log booms in two different perspectives:the log boom as a truncated line, to measure loads at its anchorage points and the motion of some modules of this line; and the log boom as a captive unity of this line, to characterize its dynamics, in a static approach, as a single bare body, in the presence of adjacent bodies, and subject to a flow with scale debris. The experiments with the truncated model helped to understand the behavior of scale log booms lines. The inclination with the flow, along with the variation of stream velocity and presence of debris, affected their load response, and their pitch and heave motion. These conclusions guided the hypothesis to design the experiments using a single captive model to measure drag, lift, and moment coefficients on the waterline plane, in a static two-dimensional approach. This second part considered variation of flow angle, flow velocity, and debris amount. The results caught the interference influence of adjacent log boom modules, the blockage effect generated by the test facility size, and the effects of debris in the log boom module resistance response.